Effects of quarter heel raising exercise on balance and ankle strength in functional ankle instability subjects - Seo, Joon Ho; Lee, Mi Young (Medicine (Baltimore), 2022)
Background: Functional ankle instability (FAI) is defined as the subjective sensation of instability or "giving way" after an ankle sprain and occurs in approximately 40% of patients with lateral ankle instability. As an ankle joint rehabilitation intervention, heel raising exercises, toe jumping exercises, ankle joint proprioceptive exercises, as well as orthosis and taping are commonly applied to prevent the recurrence of an ankle joint injury. So this study was evaluated effect of quarter heel raising exercise (QHR) on balance and peroneus longus muscle strength in FAI subjects. Methods: Among 26 FAI subjects, 13 with FAI were assigned to the QHR group, and 13 with FAI were assigned to the control group which was no intervention. All of 30 subjects were evaluated Teskscan included static balance ability, Y balance test included dynamic balance ability with three directions which is anterior, posterolateral, posteromedial direction. Commander muscle testing included eversion/inversion strength ratio at pre- and post-intervention. Results: There was a significant interaction between group and time in static, dynamic balance, and strength. In QHR group, there was simple effect on static, dynamic balance, and strength. But control group showed no simple effect on static, dynamic balance, and strength. In the pre- and post-intervention differences between the groups. There was a significant difference in pre-intervention condition between the groups, but no significant difference between the groups in post-intervention in all conditions. Conclusions: QHR exercise is useful for improving the balance ability and muscle strength of the peroneus longus muscle in FAI subjects.